2005
DOI: 10.1523/jneurosci.3293-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Naturally Occurring Variations in Maternal Care on Prepulse Inhibition of Acoustic Startle and the Medial Prefrontal Cortical Dopamine Response to Stress in Adult Rats

Abstract: In rats, naturally occurring variations in maternal care contribute to the development of individual differences in the behavioral and neuroendocrine responses to stress during adulthood. The dopamine (DA) projection to the medial prefrontal cortex (mPFC) plays an important role in mediating stress responsivity and is thought to be involved also in regulating sensorimotor gating. In the present study, we compared prepulse inhibition (PPI) of acoustic startle as well as the left and right mPFC DA stress respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
95
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(109 citation statements)
references
References 93 publications
9
95
3
Order By: Relevance
“…Likewise, mGluR1 −/− mice show impaired performance on tests of hippocampal learning and memory. The mGluR1 −/− mouse and the adult rat offspring of low-LG mothers share a common decrease in capacity in prepulse inhibition, an experimental model of sensorimotor gating (82,83) that is in part hippocampal-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, mGluR1 −/− mice show impaired performance on tests of hippocampal learning and memory. The mGluR1 −/− mouse and the adult rat offspring of low-LG mothers share a common decrease in capacity in prepulse inhibition, an experimental model of sensorimotor gating (82,83) that is in part hippocampal-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…While there is a paucity of evidence concerning asymmetry of mPFC GABA transmission (Mora et al, 1984), dopamine transmission in mPFC shows significant lateralization (Slopsema et al, 1982;Carlson et al, 1988). Furthermore, studies have shown that alterations in hemispheric asymmetry of mPFC dopamine transmission are programmed during various developmental stages in early life (Fride and Weinstock, 1988;Brake et al, 2000), including the postnatal period (Zhang et al, 2005;Sullivan and Dufresne, 2006). Thus it is possible that the hemisphere-dependent effects of FG-7142 on mPFC activity with different early rearing conditions reported here are due in part to lateralized alterations in dopamine transmission in this region.…”
Section: Discussionmentioning
confidence: 99%
“…In the PFC, there are fewer DA transporters (Sesack et al 1998) and increases in DA release to even very phasic stimulation lasts on the order of many seconds (Garris et al 1993;Lavin et al 2005). Furthermore, in response to stressful events that are presumably worse than expected, PFC DA levels measured electrochemically increase for tens of minutes past the stressful event (Doherty and Gratton 1996;Brake et al 2000;Zhang et al 2005). Therefore, even though events change firing bidirectionally in the VTA on the order of milliseconds, within the PFC the DA signal is neither temporally precise nor bidirectional in its response to events of positive and negative valence.…”
Section: Functional Implicationsmentioning
confidence: 99%